Concurrent cetuximab versus platinum‐based chemoradiation for the definitive treatment of locoregionally advanced head and neck cancer. Issue 3 (16th April 2014) - Tang, Chad; Chan, Cato; Jiang, Wen; Murphy, James D.; von Eyben, Rie; Colevas, A. Dimitrios; Pinto, Harlan; Lee–Enriquez, Nancy; Kong, Christina; Le, Quynh‐Thu
Abstract Background The purpose of this study was to present our experience utilizing cetuximab and platinum‐based concurrent chemoradiotherapy for the definitive treatment of head and neck squamous cell carcinoma (HNSCC). Methods Patients (n = 177) who received definitive concurrent chemoradiotherapy for HNSCC were stratified into 3 groups: receiving cetuximab monotherapy (n = 24), cetuximab and chemotherapy combination (n = 33), or platinum‐based chemotherapy without cetuximab (n = 120). Primary endpoints were freedom from relapse, event‐free survival, and overall survival (OS). Results Patients receiving cetuximab monotherapy were older with lower Karnofsky performance status (KPS) and higher Charlson comorbidity scores compared with those treated with combination cetuximab and chemotherapy or platinum‐based concurrent chemoradiotherapy. Patients treated with platinum‐based concurrent chemoradiotherapy exhibited significantly better freedom from relapse, event‐free survival, and OS compared with those receiving cetuximab monotherapy or cetuximab and chemotherapy combination therapies (all p < .05). Differences between patients receiving cetuximab monotherapy and platinum‐based concurrent chemoradiotherapy held on multivariate Cox regression. Conclusion This study suggests that platinum‐based concurrent chemoradiotherapy is superior to cetuximab‐based monotherapy for the definitive treatment of HNSCC. © 2014 Wiley Periodicals, Inc. Head Neck 37: 386–392, 2015